Perlindungan Hukum Terhadap Korban Kejahatan Pencemaran Nama Baik Dalam Berita Hoax di Sosial Media Twitter - Latief, Chesya Najwa; Faridah, Hana (Jurnal Ilmiah Wahana Pendidikan, 2025)
Technological developments are increasing day by day, both technology and its use, providing many positive and negative impacts. Technology also has a significant influence on the understanding of crime, especially towards schools of criminology which focus on human factors, both physical and psychological. One of the most common crimes on social media is defamation, especially on Twitter. Freedom of opinion, especially on social media, is often misused by society. because in exercising the right to freedom of opinion, people often commit acts of insults, baseless accusations and defamation, thereby harming some individuals. The research method used in this research is the normative legal method or what is usually called descriptive normative juridical research, which is research that focuses on positive legal norms, namely in the form of statutory regulations and judges' decisions. Legal research methodology along with its respective characteristics and function in analyzing contemporary legal problems, using literature studies as a basis for answering these problems. This research uses secondary data as the main data to be used as support